Synthesis and assessment of Metal-Organic Frameworks (MOFs) adsorbents for CO2 capture: A comparative work of the CO2 adsorption capability of Mono-and Bimetal-based MOFs adsorbents - Nor Khonisah, Daud; Nurul Huda Insyirah, Muhammad Najib (Universiti Putra Malaysia Press, 2025)
Adsorption utilising porous solid adsorbent has been considered a feasible option for conventional CO2 absorption over the past few decades. As a preliminary investigation towards obtaining Metal-Organic Frameworks (MOFs) adsorbent for CO2 capture, the CO2 adsorption efficiency using mono-and bimetal-based MOFs was assessed in this study. Among the numerous MOFs, Mg-MOF-74 exhibits the best CO2 uptake at low pressures because of its open metal sites. A strategy to incorporate Zn in Mg-based MOF as a co-metal node is required to enhance the CO2 adsorption performance of solid adsorbent. Selecting Zn as a metal node in MOF synthesis allows for the creation of stable, versatile, and functional materials for CO2 adsorption. Therefore, combining several metals in a structure to develop a new MOF with an improved gas uptake is quite a useful approach to further harness the immense potential of MOFs. This study aims to compare the performance of mono-and bimetallic-MOFs and select the most suitable adsorbent for CO2 capture. The performance of CO2 adsorption was conducted using three parameters: the effect of metal loading on MOFs, pressure (1–5 bar) and adsorbent dosage (0.2–0.5g). Based on the characterisation findings, the studies confirm the formation of Mg-MOF-74, ZnMOF and 50wt.%Zn/50wt.%Mg-MOF. Overall, it was found that the bimetal adsorbent with 50 wt.%Zn/50wt.%Mg-MOF displayed the highest CO2 adsorption capacity (323 mgCO2/gadsorbent) when compared to the monometallic MOFs (Zn-MOF (134mgCO2/gadsorbent) and Mg-MOF-74) (122 mgCO2/gadsorbent) indicating a 50% increase in adsorption capacity over monometallic MOFs.